Laparoscopic treatment of varicocele within adolescents in two African countries - Gbenou Antoine Seraphin; Fiogbe Michel Armand; Akakpo-Numado Gamedzi Komlatsè; Metchihoungbe Codjo Serge; Uroz Tristan Jos (Wolters Kluwer Medknow Publications, 2019)
Varicocele is often ignored by adolescents and their parents, in our context. The aim of the study is to present the indications and results of laparoscopic treatment in a population of adolescent students. Subjects and Methods: It is a descriptive and analytical prospective study over a period of 9 months (January to September 2013), focussed on cases of varicocele Grade 3 found in adolescents during a screening, and who underwent surgical treatment by laparoscopy. The laparoscopic treatment was done as part of a training mission to paediatrics surgeons, through a European Non-governmental organisation in two university hospitals in Africa. Of 2724 adolescent students examined, 149 (5.47%) had a varicocele. The average age was 16.39 ± 2.05 years (12 and 19). The side was unilateral (79.19%) with 76.51% left or bilateral (20.81%) (P = 0.00). According to the classification of Dubin and Amelar, there were 58 (38.92%) cases of Grade 1, 66 (44.30%) were Grade 2 and 25 (16.78%) were Grade 3. Results: The laparoscopic treatment was performed in 23 patients with varicocele Grade 3, by modified Palomo's technique, sectioning a segment of vessels between clips (15) between nodes (2) or after coagulation without clips and ligation (6). The hospital stay was 36 h. It has been observed one case of post-operative moderate vaginal hydrocele and 11 cases testicular hypertrophy. Conclusion: The laparoscopic treatment of varicocele in adolescents reduces post-operative morbidity related to conventional open surgery. This technique has been available in two poor African countries through partnership north-south.